Manajemen Sarana dan Prasarana Perspektif Pendidikan Islam dalam Mewujudkan Sekolah Bermutu - Sarif Hidayatulloh; Sedya Santosa; Rangga Pratama Saputra; Nadilla Aleyda Maqhfira Agustin; Dinda Agustiana (Yayasan Al-Afif, 2026)
Facilities and infrastructure management is one of the important factors in improving the quality of education in schools. This study aims to describe the implementation of facilities and infrastructure management from the perspective of Islamic education in realizing a quality school at SMP Negeri 4 Simpangkatis. This study employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving the principal, vice principal, teachers, and administrative staff. The data were analyzed using the Miles and Huberman model through data reduction, date presentation, and conclusion drawing. The results showed that the management of facilities and infrastructure was carried out through planning, procurement, utilization, maintenance, and supervision of school facilities. The implementation reflected Islamic educational values such as trustworthiness, deliberation, responsibility, and cleanliness, thereby supporting the creation of a conducive learning environment and the realization of a quality school.